2021
DOI: 10.1177/0192513x21994135
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-Origin College Students’ Stress, Sibling Relationships, Academic Motivation, and Depressive Symptoms

Abstract: The current study investigated associations among interpersonal, academic, financial, and ethnicity-related stressors and college students’ academic motivation and depressive symptoms, as well as the moderating role of positive sibling relationships on these associations. Participants included 171 Mexican-origin college students (80.7% female; M = 21.6 years). Data were collected using an online survey and analyzed with path analysis. Under conditions of more positive sibling relationships, there was a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The NRI has been used extensively in Latinx populations in the United States. For instance, the NRI has been used to assess sibling (Jones et al, 2022), romantic partner (Killoren et al, 2022), and parent (Chancy et al, 2022) relationship qualities in samples of Latinx adolescents and young adults. Across studies, reliability has been good (α = .83–.95), and validity has been established in its association with outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The NRI has been used extensively in Latinx populations in the United States. For instance, the NRI has been used to assess sibling (Jones et al, 2022), romantic partner (Killoren et al, 2022), and parent (Chancy et al, 2022) relationship qualities in samples of Latinx adolescents and young adults. Across studies, reliability has been good (α = .83–.95), and validity has been established in its association with outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Struthers et al (2000) found that stress positively predicted motivation in Canadian college students, and Park et al (2012) reported that the academic motivation scale "extrinsic identified regulation" was positively related to stress in Korean medicine students. Furthermore, interpersonal stress was positively associated with academic motivation in Mexican-origin college students but only under the condition of a positive sibling relationship (Jones et al, 2022). In Nigerian students, intrinsic motivation and academic stress were also positively related (Muza and Muhammad, 2020).…”
Section: Prediction Of Academic Motivationmentioning
confidence: 98%
“…Research in latin America mentions that students' academic stress during the pandemic stems from piling up tasks, family factors, boyfriend or girlfriend communication barriers, and the problem of declining financial income [36]. Academic stress is a psychic turmoil that impacts the emergence of mental and physical health problems.…”
Section: Student Academic Stress During the Covid-19 Pandemicmentioning
confidence: 99%
“…Stressors during the dominant pandemic resulted from lockdowns, uncertainty over the cessation of the COVID-19 virus, financial constraints, and online learning. Students must guarantee an internet connection because online lectures are more than 6-8 hours daily, plus many assignments and isolation [71] [36]. The COVID-19 International Student Wellbeing Study (C19 ISWS), through a sample of 2,480 students at InHolland Universities of Applied Sciences in the Netherlands, was found to experience stress, depression, and loss of resilience due to online learning [72].…”
Section: Student Academic Stress During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation